Co‐administration of Antimicrobial Peptides Enhances Toll‐like Receptor 4 Antagonist Activity of a Synthetic Glycolipid. (24th January 2018) - Facchini, Fabio A.; Coelho, Helena; Sestito, Stefania E.; Delgado, Sandra; Minotti, Alberto; Andreu, David; Jiménez‐Barbero, Jesús; Peri, Francesco
Abstract: This study examines the effect of co‐administration of antimicrobial peptides and the synthetic glycolipid FP7, which is active in inhibiting inflammatory cytokine production caused by TLR4 activation and signaling. The co‐administration of two lipopolysaccharide (LPS)‐neutralizing peptides (a cecropin A–melittin hybrid peptide and a human cathelicidin) enhances by an order of magnitude the potency of FP7 in blocking the TLR4 signal. Interestingly, this is not an additional effect of LPS neutralization by peptides, because it also occurs if cells are stimulated by the plant lectin phytohemagglutinin, a non‐LPS TLR4 agonist. Our data suggest a dual mechanism of action for the peptides, not exclusively based on LPS binding and neutralization, but also on a direct effect on the LPS‐binding proteins of the TLR4 receptor complex. NMR experiments in solution show that peptide addition changes the aggregation state of FP7, promoting the formation of larger micelles. These results suggest a relationship between the aggregation state of lipid A‐like ligands and the type and intensity of the TLR4 response. Abstract : Working well together : Co‐administration of the synthetic glycolipid FP7 and cationic antimicrobial peptide (AMPs) potentiates the antagonist effect of FP7 on toll‐like receptor 4 (TLR4). This synergy is observed in cells stimulated with lipopolysaccharide (LPS) and also with a non‐LPS agonist, phytohemagglutinin. The results suggest a complex mechanism of action based on the binding of AMPs to the TLR4–MD‐2 complex, and/or on the FP7 aggregation state.